2013
DOI: 10.1002/mus.23699
|View full text |Cite
|
Sign up to set email alerts
|

Spasticity, weakness, force variability, and sustained spontaneous motor unit discharges of resting spastic–paretic biceps brachii muscles in chronic stroke

Abstract: Introduction The purpose was to examine relations among spasticity, weakness, force variability, and sustained spontaneous motor unit discharges in spastic-paretic biceps brachii muscles in chronic stroke. Methods Ten chronic stroke subjects produced submaximal isometric elbow flexion force on impaired and non-impaired sides. Intramuscular EMG (iEMG) was recorded from biceps and triceps brachii muscles. Results We observed sustained spontaneous motor unit discharges in the resting biceps on iEMG. Spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 22 publications
(71 reference statements)
4
71
0
1
Order By: Relevance
“…Movement variability is also critical for responding to permutations in the environment and producing on-line corrections [44,50,51]. On the other hand, pathologically increased movement variability has been characterized in many neurologic conditions, including Parkinson disease [52][53][54][55][56], stroke [39,57], dystonia [41,58], developmental coordination disorder [59,60], and cerebral palsy [61,62], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Movement variability is also critical for responding to permutations in the environment and producing on-line corrections [44,50,51]. On the other hand, pathologically increased movement variability has been characterized in many neurologic conditions, including Parkinson disease [52][53][54][55][56], stroke [39,57], dystonia [41,58], developmental coordination disorder [59,60], and cerebral palsy [61,62], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Although various motor abilities are required in steady force production tasks, the motor control deficits after stroke have been typically captured through a few indexes such as the steadiness of the finger force (Kurillo et al 2004;Lodha et al 2010Lodha et al , 2012Naik et al 2011;Lindberg et al 2012;Chang et al 2013). Other motor abilities such as accuracy, reproducibility, flexibility, or multiformity are not well understood in the stroke population, although one previous study reported that stroke survivors retained multiformity in reaching tasks (Reisman and Scholz 2003) while still showing deficits in reproducibility (Reisman and Scholz 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For all structural components of endpoint jerk, non-parametric INT-RT1 analysis found significant main effects of impairment group [F (2,27) . With regards to the interaction between impairment group and movement direction, NI and HSMOD subjects had higher ∫ (t) 2 and ∫ (t) 2 contributions (and lower ∫ (t) 2 contributions) for movements to the L ELBOW target than movements to the H MULTI movements (Fig.…”
Section: Movement Kinematics-experimentsmentioning
confidence: 99%
“…This claim rests on the premise that in order to fully compensate for any given load, weaker muscles require more activation than stronger muscles, and greater voluntary contractions give rise to greater levels of "signal dependent noise", which in healthy subjects manifests as a linear scaling of force variability with respect to the mean force level. 26 Indeed, a study of isometric force production in the paretic-spastic biceps brachii muscle 27 found that greater muscle weakness led to greater variability in the generation of muscle force (i.e., greater motor noise). Increased force production variability has similarly been observed at the wrist and fingers post-stroke.…”
Section: Introductionmentioning
confidence: 99%